T cell responses to D-penicillamine in drug-induced myasthenia gravis: recognition of modified DR1:peptide complexes. - Hill, M; Moss, P; Wordsworth, P; Newsom-Davis, J; Willcox, N (1999)
The anti-rheumatoid drug D-penicillamine (D-pen) has a reactive sulfhydryl group capable of modifying self antigens, and can provoke typical autoantibody-mediated myasthenia gravis (MG), especially in DR1+ individuals. We have selected T cell clones from one such patient that were highly specific for D-pen but not its L-isomer or D-cysteine. Moreover, they were restricted to HLA-DR1, had a Th1 phenotype and used TCR V alpha4.1, V beta6.1. They responded well to blood mononuclear cells prepulsed with D-pen either in the absence of serum or after chloroquine treatment, but not to autologous D-pen-pulsed B cell lines. Thus, D-pen may directly couple to distinctive peptides resident in surface DR1 molecules on circulating macrophages or dendritic cells.